The search for new meaning : adolescent bereavement after the sudden death of a sibling : a grounded theory study - Forward, Debbie, 1958- (2001)
Thesis (M.Ed.)--Memorial University of Newfoundland, 2001. Education Bibliography: leaves 112-123 Despite the fact that many adolescents experience the sudden death of a brother or sister, little is known about the bereavement process. The purpose of this study was to use a grounded theory approach to examine the bereavement process for adolescents who experienced the sudden death of a sibling. Interviews conducted with six adolescents, within seven years of their sibling's death, provided the major sources of data. The findings of this study indicate that the bereavement process is variable and encompasses five stages. In each of these stages the adolescent focuses on the basic psychological process of 'the search for new meaning'. The first stage, 'finding out', encompasses the teens initial reactions to hearing of their sibling’s death. 'Avoiding reality', stage two, is a time when the adolescent has not really accepted that their sibling is gone, and is marked by either numbness or keeping busy. The third stage, 'facing reality', is the focal point of the bereavement process. Three key obstacles are identified: dealing with the pain; intense loneliness; and, being different. The teens then 'turn the corner' and go in one of two directions. The teens either realize they can survive within the reality of the loss and move on to the 'finding new meaning’ stage, or they give up and 'end their search'. Key elements of the 'finding new meaning' stage are: accepting the pain; continuing the bond; and, redefining self. Even after 'finding new meaning', the teens can return to the 'facing reality' stage and continue their search if their new meaning does not allow them to move on with their lives. Findings from this study may give new insights into developing interventions for helping teens through this bereavement process that is grounded in scientific rationale and is age sensitive, addressing adolescents unique experiences and concerns. Included in this study are implications for practice, education and research for helping professionals.